Performance of physiological basis of rice hybrids under system of rice cultivation (Bangladesh Journal of Botany, 2015)
Among the rice hybrids, PRH-10 recorded significantly highest chlorophyll content, dry matter, LAI, CGR, RGR, NAR, root length, root: shoot ratio and grain yield (9.95 t/ha) over the rest of hybrids followed by NPH-567. The lowest values of these parameters were noted in IR-36. The higher straw yield was recorded (144.8 t/ha) in NPH-567. DOI: http://dx.doi.org/10.3329/bjb.v43i3.21614 Bangladesh J. Bot. 43(3): 359-361, 2014 (December)